Isomerism and dynamic behavior of bridging phosphaalkynes bound to a dicopper complex. Issue 6 (8th January 2020) - Nicolay, Amélie; Ziegler, Micah S.; Small, David W.; Grünbauer, Rebecca; Scheer, Manfred; Tilley, T. Don
Abstract : A dicopper complex featuring a symmetrically bridging nitrile ligand and supported by a binucleating naphthyridine-based ligand was treated with phosphaalkynes to yield dicopper complexes that exhibit phosphaalkynes in rare μ-η 2 : η 2 binding modes. Abstract : A dicopper complex featuring a symmetrically bridging nitrile ligand and supported by a binucleating naphthyridine-based ligand, [Cu2 ( μ-η 1 : η 1 -MeCN)DPFN](NTf2 )2, was treated with phosphaalkynes (RCP, isoelectronic analogues of nitriles) to yield dicopper complexes that exhibit phosphaalkynes in rare μ-η 2 : η 2 binding coordination modes. X-ray crystallography revealed that these unusual "tilted" structures exist in two isomeric forms (R "up" vs. R "sideways"), depending on the steric profile of the phosphaalkyne's alkyl group (R = Me, Ad, or t Bu). Only one isomer is observed in both solution and the solid state for R = Me (sideways) and t Bu (up). With intermediate steric bulk (R = Ad), the energy difference between the two geometries is small enough that both are observed in solution, and NMR spectroscopy and computations indicate that the solid-state structure corresponds to the minor isomer observed in solution. Meanwhile, treatment of [Cu2 ( μ-η 1 : η 1 -MeCN)DPFN](NTf2 )2 with 2-butyne affords [Cu2 ( μ-η 2 : η 2 -(MeCCMe))DPFN](NTf2 )2 : its similar ligand geometry demonstrates that the tilted μ-η 2 : η 2 binding mode is not limited to phosphaalkynes but reflects a more general trend, which can be rationalized via an NBO analysis showing maximization of π-backbonding.